EVALUATION OF FLUID/FLUID INTERACTIONS DURING LOW SALINITY WATER FLOODING. - Villero Mandon, Jose Daniel (Nazarbayev University School of Mining and Geosciences, 2024)
Low-salinity water flooding/smart water flooding (LSWF/SWF) involves injecting water with an altered composition to modify the equilibrium between rock and fluids within porous media, particularly for enhanced oil recovery (EOR) due to improved extraction efficiency. This technology offers significant advantages, being environmentally friendly and often more economically efficient. LSWF/SWF has been shown to increase recovery factor (RF) between 6% and 20% in oil-wet rocks, making it an appealing option, especially for sandstones with low clay content, which tend to be water-wet. While most studies focus on rock/fluid interactions as the primary mechanism, this study explores the effects of LSW mechanisms on the brine/oil interface alongside rock surface interactions and the synergistic effects of a hybrid EOR approach. Initially, ions were classified into three groups: monovalent cations (Na+, K+), divalent cations (Mg2+, Ca2+), and anions (SO42-). Ten different brines with varying ionic compositions and strengths were then prepared and screened based on interfacial tension (IFT), microdispersions generation, and rheological properties measurements to identify the optimal scenario for LSWF/SWF and observe the effects of different concentrations (7500 and 5000 ppm) on fluid/fluid interactions. The best option identified was further investigated in core flooding experiments conducted at 11500 ppm, 8500 ppm, and 1000 ppm to evaluate LSW/SWF flooding under different conditions and design techniques. Key findings include the observation that a single ion configuration brine approach may be not as as representative of interactions in brine/oil interface. IFT is highly dependent on asphaltene content, with lower asphaltene content yielding better results in IFT with more complex brines. Salinity was found to increase IFT by approximately 1 mN/m per 1000 ppm. As the anions in the salts increased, the interface became more viscoelastic and resilient to snap-off (capillary forces drive the wetting phase to infiltrate, displacing the initial nonwetting phase as presented by Li & Yao 2023 ) occurrence, while changes in salinity had minimal impact on the storage modulus. The microemulsion volume fraction increased depending on the asphaltene content, with an increasing colloidal instability index (CII) directly impacting the volume of emulsions. Overall, fluid/fluid interactions were found to be more related to LSWF/SWF in different oil samples with different content of asphaltenes and different compositions. For core-flooding, comparingcores with same rock type, but different fluid injection, an additional 4.1% Original Oil in Place (OOIP) was achieved due to improved fluid/fluid interactions, with tertiaty flooding recovering an additional 1.8% OOIP, representing an efficiency improvement of roughly 15% compared to NaCl alone, solely attributed to an enhanced interface. Low salinity water below the critical salinity concentration (CSC) resulted in an additional 0.7% OOIP recovery, representing 3.55% of residual OOIP. This methodology proved to be innovative and feasible for fluid/fluid interactions and can be extrapolated for rock/fluid interactions.
Keywords: fluid-fluid interaction; water wet sandstones; low salinity waterflood; IFT reduction; Viscoelastic behavior; Microemulsion; Type of access: Restricted